Route of chronic kidney patients foreigners in the search for health care in a border area - Ederson Pereira; Mariana Alvina dos Santos; Manoela de Carvalho (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to describe the journey of foreigners with chronic kidney diseases searching for treatment in the Brazilian Unified Health System in a border area. Methods: this is a qualitative research conducted with thirteen foreign participants. Data were collected by interviews and analyzed based on the theoretical-methodological framework of the therapeutic itinerary. Results: empirical evidence showed seven thematic categories, indicating poor illness perception; poor family support throughout treatment; social aspects such as work, income, and housing as sources of distress; search for alternative treatments; interrupted search for healthcare abroad due to financial problems; journey to healthcare-seeking in Brazil eased by family members and social networks. Final considerations: the asymmetries within the Paraguayan and Brazilian health systems spur the search for cross-border integration actions. Identifying another country's assistance aspects may help in planning more welcoming policies in border regions.